A growing family of outcome measurement proposals for hidradenitis suppurativa. (1st May 2021) - Emtestam, L.; Lapins, J.; Sartorius, K.
Abstract: Linked Article: Goldfarb et al. Br J Dermatol 2021; 184 :905–912 .